Conquering the Tyranny of Number With Digital Microfluidics - Yang, Ya-Tang; Ho, Tsung-Yi (Frontiers in Chemistry, 2021)
The development of large-scale integration (LSI) based on soft lithography has ushered a new revolution in microfluidics. This technology, however, relies inherently on pneumatic control of micromechanical valves that require air pressure to operate, while digital microfluidics uses a purely electrical signal on an electrode for droplet manipulation. In this article, we discuss the prospect and current challenges of digital microfluidics to solve the problem of the tyranny of numbers in arbitrary fluidic manipulation. We distill the fundamental physics governing electrowetting and their implications for specifications of the control electronics. We survey existing control electronics in digital microfluidics and detail the improvements needed to realize a low-power, programmable digital microfluidic system. Such an instrument would attract wide interest in both professional and non-professional (hobbyist) communities.